HUBUNGAN ANTARA STRATEGI COPING DENGAN BURNOUT PADA GURU TK SE-KECAMATAN TAMPAN KOTA PEKANBARU - Nensi Villanesia Nensi Villanesia; Daviq Chairilsyah Daviq Chairilsyah; Devi Risma Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The teacher is a profession that is at high risk for developing chronic job stress that it is possible to cause burnout. To control emotions can be done in many ways, one way of coping strategies. Is a way of coping strategies or behaviors of individuals to solve a problem. This study aims to determine whether there is a relationship between coping strategies with burnout. This study is aimed at kindergarten educators district Tampan City Pekanbaru, with a population of 158 people and a sample of 62 people. Data collection techniques using questionnaires. The analysis showed that the kindergarten educators district Tampan City Pekanbaru using both types of coping strategies with the medium category, problem-focused coping as many as 20 people with a percentage of 32,3% and emotional-focused coping as many as 42 people by 67,7%. Burnout produced, including in the medium category of 62 people with a percentage (100%).Keywords: coping strategies, burnout, teacher